Press "Enter" to skip to content

Download e-book for kindle: Algorithms - Sequential, Parallel - A Unified Appr. by R. Miller, L. Boxer

By R. Miller, L. Boxer

Show description

Read or Download Algorithms - Sequential, Parallel - A Unified Appr. PDF

Best algorithms books

Algorithmic and Analysis Techniques in Property Testing by Dana Ron PDF

Estate trying out algorithms convey a desirable connection among worldwide homes of items and small, neighborhood perspectives. Such algorithms are "ultra"-efficient to the level that they just learn a tiny component to their enter, and but they come to a decision no matter if a given item has a definite estate or is considerably assorted from any item that has the valuables.

Download e-book for kindle: Graph Data Model: and Its Data Language by Hideko S. Kunii (auth.)

Advanced databases might be understood good with visible illustration. A graph is a really intuitive and rational constitution to visually characterize such databases. Graph facts version (GDM) proposed by way of the writer formalizes info illustration and operations at the facts by way of the graph idea. The GDM is an extension of the relational version towards structural illustration.

New PDF release: Digital Fourier Analysis: Fundamentals

This textbook is a radical, obtainable creation to electronic Fourier research for undergraduate scholars within the sciences. starting with the foundations of sine/cosine decomposition, the reader walks in the course of the ideas of discrete Fourier research earlier than achieving the cornerstone of sign processing: the quick Fourier remodel.

Extra resources for Algorithms - Sequential, Parallel - A Unified Appr.

Sample text

Then prove by substitution. 1. Upper bound: Guess: T (n) ≤ dn lg n. Substitution: T (n) ≤ T (n/3) + T (2n/3) + cn ≤ d(n/3) lg(n/3) + d(2n/3) lg(2n/3) + cn = (d(n/3) lg n − d(n/3) lg 3) + (d(2n/3) lg n − d(2n/3) lg(3/2)) + cn = dn lg n − d((n/3) lg 3 + (2n/3) lg(3/2)) + cn = dn lg n − d((n/3) lg 3 + (2n/3) lg 3 − (2n/3) lg 2) + cn = dn lg n − dn(lg 3 − 2/3) + cn ≤ dn lg n if −dn(lg 3 − 2/3) + cn ≤ 0 , c . d ≥ lg 3 − 2/3 Therefore, T (n) = O(n lg n). , d) are different. 2. Lower bound: Guess: T (n) ≥ dn lg n.

We have T (n) ≥ c(n − 2) lg(n − 2) + d(n − 2) + 2 lg n = cn lg(n − 2) − 2c lg(n − 2) + dn − 2d + 2 lg n > cn lg(n − 2) − 2c lg n + dn − 2d + 2 lg n (since − lg n < − lg(n − 2)) = cn lg(n − 2) − 2(c − 1) lg n + dn − 2d ≥ cn lg(n/2) − 2(c − 1) lg n + dn − 2d (by inequality (1) above) = cn lg n − cn − 2(c − 1) lg n + dn − 2d ≥ cn lg n , if −cn−2(c−1) lg n+dn−2d ≥ 0 or, equivalently, dn ≥ cn+2(c−1) lg n+2d. Pick any constant c > 1/2, and then pick any constant d such that d ≥ 2(2c − 1) . ) Then d/2 ≥ 2c − 1 = c + (c − 1) , and adding d/2 to both sides, we have d ≥ c + (c − 1) + d/2 .

1. 2. 3. 4. The following justiÞcations explain some of the rankings: 1. en = 2n (e/2)n = ω(n2n ), since (e/2)n = ω(n). 2. (lg n)! = ω(n 3) by taking logs: lg(lg n)! = approximation, lg(n3 ) = 3 lg n. lg lg n = ω(3). (lg n lg lg n) by Stirling’s Solutions for Chapter 3: Growth of Functions 3-11 √ √ √ √ 3. ( 2)lg n = ω 2 2 lg n by taking logs: lg( 2)lg n = (1/2) lg n, lg 2 2 lg n = 2 lg n. (1/2) lg n = ω( 2 lg n). √ √ 4. 2 2 lg n = ω(lg2 n) by taking logs: lg 2 2 lg n = 2 lg n, lg lg2 n = 2 lg lg n.

Download PDF sample

Rated 4.36 of 5 – based on 27 votes